Influence of Infotainment-System Audio Cues on the Sound Quality Perception Onboard Electric Vehicles in the Presence of Air-Conditioning Noise - Massimiliano Masullo; Katsuya Yamauchi; Minori Dan; Federico Cioffi; Luigi Maffei (Acoustics)
Car cabin noise generated by heating, ventilation, and air-conditioning (HVAC) systems significantly impacts passengers’ acoustic comfort. In fact, with the reduction in engine noise due to the passage from internal combustion to electric or hybrid-electric engines, interior background noise has dramatically reduced, especially at 25% and 50% HVAC airflow rates. While previous research has focused on the effect of HVAC noise in car cabins, this paper investigates the possibility of using car infotainment-system audio cues to moderate onboard sound quality perception. A laboratory experiment combining the factors of infotainment-system audio (ISA) cues, signal-to-noise ratios (SNRs), and airflow rates (AFRs) at different levels was performed in two university laboratories in Italy and Japan involving groups of local individuals. The results indicate that introducing ISA cues in car cabins fosters improvements in the perceived aesthetic dimension of sound quality, making it more functioning, natural, and pleasant. For the Italian group, adding ISA cues also moderated the loudness dimension by reducing noise perception. The moderating effects of ISA cues differed between the Italian and Japanese groups, depending on the AFR. All these effects were more evident at the SNR level of −4 dB when the ISA cues competed with existing background noise.